Analysis of the economic, labour, and management effects of COVID-19 on rural accommodation: An application to a rural European province (Cáceres, Spain) - Marcelino Sánchez-Rivero; M Cristina Rodríguez-Rangel; Paloma García Cerro; Ana M Manjón García (Administrative Sciences, 2022)
The COVID-19 pandemic has changed the consumption habits of tourists to benefit sustainable destinations that are not overcrowded, such as rural tourism destinations. However, the periods of compulsory lockdown have had devastating effects on tourism businesses operating in rural areas and have even jeopardised their economic viability. The aim of this article is to quantify in relative terms the effects that the period of compulsory lockdown in a markedly tourist country, such as Spain, between March and May 2020 has had on rural accommodation in one of the most rural provinces of Spain (Cáceres). Based on a random sample of 225 rural accommodation establishments and the consideration of various factors, statistical techniques of comparison of means and proportions were used to detect differences in the intensity of the effects of the compulsory lockdown on the economic-financial management, bookings, facilities, and input of rural accommodation establishments in the province. The results obtained show that the economic, labour, and management effects of the COVID-19 pandemic on rural tourism businesses in the province of Cáceres have been very substantial. In particular, the businesses with the highest level of tourist services on supply, i.e., those that, in addition to accommodation, also offer other tourist activities, have been the most affected. In view of this situation, urgent emergency measures have been put in place at a provincial level to alleviate the economic loss and the destruction of jobs caused by this pandemic.
Keywords: 350; COVID-19 effects; labour market; Cáceres; mean comparison; proportion comparison; political actions